Centralized laboratory a boon to research & testing activities - UMP, PNC
Universiti Malaysia Pahang (UMP) recently launched the Centralized Laboratory, which is expected to be the one-stop referral point for industrial product research and testing in the country, especially in the East Coast of Peninsular Malaysia.